Detecting the influence of fossil fuel and bio-fuel black carbon aerosols on near surface temperature changes - G. S. Jones; N. Christidis; P. A. Stott (Atmospheric Chemistry and Physics, 2011)
Past research has shown that the dominant influence on recent global climate changes is from anthropogenic greenhouse gas increases with implications for future increases in global temperatures. One mitigation proposal is to reduce black carbon aerosol emissions. How much warming can be offset by controlling black carbon is unclear, especially as its influence on past climate has not been previously unambiguously detected. In this study observations of near-surface warming over the last century are compared with simulations using a climate model, HadGEM1. In the simulations black carbon, from fossil fuel and bio-fuel sources (fBC), produces a positive radiative forcing of about +0.25 Wm−2 over the 20th century, compared with +2.52 Wm−2 for well mixed greenhouse gases. A simulated warming of global mean near-surface temperatures over the twentieth century from fBC of 0.14 ± 0.1 K compares with 1.06 ± 0.07 K from greenhouse gases, −0.58 ± 0.10 K from anthropogenic aerosols, ozone and land use changes and 0.09 ± 0.09 K from natural influences. Using a detection and attribution methodology, the observed warming since 1900 has detectable influences from anthropogenic and natural factors. Fossil fuel and bio-fuel black carbon is found to have a detectable contribution to the warming over the last 50 yr of the 20th century, although the results are sensitive to the period being examined as fBC is not detected for the later fifty year period ending in 2006. The attributed warming of fBC was found to be consistent with the warming from fBC unscaled by the detection analysis. This study suggests that there is a possible significant influence from fBC on global temperatures, but its influence is small compared to that from greenhouse gas emissions.